2017
DOI: 10.1039/c6ra25771b
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and electromechanical behavior of Nafion-based soft actuators with PPy/CB/MWCNT nanocomposite electrodes

Abstract: In this work, as an alternative to precious platinum electrodes in IPMC actuators, PPy/CB/MWCNT electrode actuators were successfully fabricated by electropolymerization of PPy on both sides of the CB/MWCNT-coated Nafion membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 61 publications
(64 reference statements)
0
43
0
Order By: Relevance
“…According to the Diaz polymerization mechanism, better PPy films with improved properties (e.g., adhesion to an electrode and uniformity) were obtained with 3% water in the AN solvent . Because the conductivity and capacitive behavior of the prepared sample could be affected by the electropolymerization conditions of PPy, optimized conditions were used here. The electropolymerization of PPy was carried out for a definite time under the optimized conditions (polymerization = 1 h, concentration of Py monomer = 0.1 M , concentration of electrolyte = 0.1 M , constant current = 2 mA/cm 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…According to the Diaz polymerization mechanism, better PPy films with improved properties (e.g., adhesion to an electrode and uniformity) were obtained with 3% water in the AN solvent . Because the conductivity and capacitive behavior of the prepared sample could be affected by the electropolymerization conditions of PPy, optimized conditions were used here. The electropolymerization of PPy was carried out for a definite time under the optimized conditions (polymerization = 1 h, concentration of Py monomer = 0.1 M , concentration of electrolyte = 0.1 M , constant current = 2 mA/cm 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…IPMCs containing higher concentration of ionic liquid exhibited more capacitor-like behavior which leads to a larger electromechanical response. Li ion was used at the present work for the ion exchange process, causing a large and fast bending of IPMC due to its small size [29]. The fast response of the IPMC also inhibited it to display any back relaxation which usually occurs with larger ions [30].…”
Section: Voltage-angle Characterizationmentioning
confidence: 99%
“…This is possible because EAP-based actuators have one continuous body which means that there are less parts needed to be assembled, and it also simplifies the programming of its movements (Alici, 2018). Ionic polymer metal composite (IPMC) actuators are EAPs that have been studied extensively in literature, but these devices require its electrodes to be made with either gold or platinum and therefore are too expensive to mass produce (Bhandari et al, 2012;Lee et al, 2013;Kotal et al, 2016;Rasouli et al, 2017;Hu et al, 2019). Alternatively, conductive polymer (CP) actuators can be used instead.…”
Section: Introductionmentioning
confidence: 99%
“…Nafion-based solid polymer electrolyte (SPE) with electrodes have been extensively used since Nafion is widely available and is biocompatible (Lee et al, 2013;Kotal et al, 2016;Rasouli et al, 2017). However, many studies have reported that combining Nafion with CP electrodes will result in poor actuations at low voltages (Lee et al, 2013;Vreeland et al, 2015;Rasouli et al, 2017;Hu et al, 2019). One study coated the Nafion surface with carbon nanotubes (CNTs) and carbon black (CB) ink before polymerizing the membrane with CP electrodes, but found this method showed unnoticeable tip displacements below 2.0 V (Rasouli et al, 2017).…”
Section: Introductionmentioning
confidence: 99%